ADOPSI PETANI TERHADAP PELAKSANAAN KONSEP PENGENDALIAN HAMA TERPADU TANAMAN BAWANG MERAH (Allium cepa var. aggregatum L.) DI DESA SOLOVE KABUPATEN SIGI - Salingkat, Satrio Wibowo; Anshary, Alam; Shahabuddin, Shahabuddin (AGROTEKBIS, 2017)
This study aimed to assess the differences in the level of farmers adoption of Integrated Pest Management component between farmers Alumni Field School Integrated Pest Management (SLPHT) and the farmers who haveânt followed the SLPHT onion crop. The research method used in the form of a random survey by interviewing respondents directly to the with to the Â question that has been presented in the questionnaire. Sample of respondents farmers by 40 people consisting of 20 farmers SLPHT and 20 farmer non-SLPHT. The results showed that the rate of adoption ofÂ  SLPHT farmers are higher than non-SLPHT farmers with an average value is 14,30 (SLPHT) to 10,25 (Non SLPHT) and there is a significant relationship pbetween the factors that influence the rate of adoption by farmers adoption SLPHT of the components of IPM relative gain factor (6.73), compatibility (6.99), complexity (10, 65), triabilitas ( 15.38), observability (14.17) and the decision of innovation (9.37).Â Key Words : Adoption, farmers, Integrated Pest Management, Onion.